2019
DOI: 10.4235/agmr.19.0037
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Solutions for Improving Pain Management Practices in Acute Hospital Settings: Perspectives of Healthcare Practitioners for a Pain-Free Hospital Initiative

Abstract: Background: Effective pain management is a fundamental human right. However, global disparities in pain management practices exist across health settings. This study explored healthcare practitioners' views on pain management in the acute care hospital setting. Methods: The focus groups included clinical specialties most likely to encounter patients with 'difficult to manage pain', namely those in the Geriatrics and Palliative Care Unit (2 doctors and 3 nurses), Critical Care Unit (7 doctors), and the Pain Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 11 A previous report described clinicians’ attitudes toward pain typically focused on pathophysiology first rather than the quality of life linking to cultural, societal and other factors. 12 Management of cancer pain should be proactive and driven by an understanding of pain mechanisms; and it should include the optimal use of multimodality interventions provided by a consultation with pain or palliative medicine physicians. 13 Studies have shown that pharmacists can have a positive impact on clinical care by leading or collaborating with interdisciplinary teams to identify drug-related problems.…”
Section: Introductionmentioning
confidence: 99%
“… 11 A previous report described clinicians’ attitudes toward pain typically focused on pathophysiology first rather than the quality of life linking to cultural, societal and other factors. 12 Management of cancer pain should be proactive and driven by an understanding of pain mechanisms; and it should include the optimal use of multimodality interventions provided by a consultation with pain or palliative medicine physicians. 13 Studies have shown that pharmacists can have a positive impact on clinical care by leading or collaborating with interdisciplinary teams to identify drug-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Acute pain management is a core ethical concept in medical practice (1). During thoracentesis and abdominocentesis, pain management is routinely managed with 1% lidocaine with a 25 gauge needle for skin and a smaller gauge needle for deeper tissue (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…During thoracentesis and abdominocentesis, pain management is routinely managed with 1% lidocaine with a 25 gauge needle for skin and a smaller gauge needle for deeper tissue (2,3). As the anesthetic injection is painful in and of itself (4), during these two procedures, pain management can sometimes fall short due to a lack of education and incorrect personal opinions (1,5). One such example is "one needle insertion can cause less pain than two-needle insertions" (5).…”
Section: Introductionmentioning
confidence: 99%
“…I read the article by Akbar et al 1 ) with great interest, as chronic pain in older persons is one of the most common conditions encountered by healthcare professionals, especially in acute-care hospitals. However, it is the least-heeded problem in hospitals, nursing homes, and home care.…”
mentioning
confidence: 99%